Risk Committee, Firm Life Cycle, and Market Risk Disclosures - Hadi-Al, A.; Hasan, Mostafa; Habib, A. (Blackwell Publishing, 2015)
Manuscript Type – Empirical. Research Question/Issue - This study investigates whether the existence of a separate risk committee and risk committee characteristics are associated with market risk disclosures. It also tests whether the role of a risk committee in affecting market risk disclosures varies for different firm life cycle stages. Research Findings/Insights - Using 677 firm-year observations of financial firms from Gulf Cooperation Council (GCC) countries during the years 2007–2011, we find that firms with a separate risk committee are associated with greater market risk disclosures, an effect that is more pronounced for mature-stage firms. Furthermore, findings suggest that risk committee qualifications and size have a significant positive impact on market risk disclosures. Theoretical/Academic Implications - This study complements the corporate governance literature by incorporating agency theory, legitimacy theory, stakeholder theory, and the resource-based theory to provide more robust evidence of the impact of a separate risk committee and the firm life cycle on market risk disclosures. Our results support the monitoring effect of a separate risk committee and suggest that a separate risk committee can improve “firm-level corporate governance” in the GCC countries characterized by a poor informational environment. Practitioner/ Policy Implications - Findings from this study provide evidence that the existence, qualifications, and size of risk committees may be used as a channel to improve the disclosure level, suggesting a policy prescription for regulators and policymakers. Investors may also find these results useful in forming their own expectations about firm-level risk disclosures.